EFEKTIFITAS PEMIJATAN PADA BAYI TERHADAP PENINGKATAN BERAT BADAN BAYI USIA 3- 5 BULAN DI WILAYAH KERJA PUSKESMAS TAPIAN DOLOK KABUPATEN SIMALUNGUN - Parmiana Bangun; Renny Sinaga (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
Development of a person is at the age of 0-12 months. It is said to be the golden age because infancy is very short and cannot be repeated. One form of stimulation that has been carried out by the community is baby massage. Baby massage is a tactile stimulation that canstimulate muscles, bones and organ systems to function optimally. Methods This research uses a quasi-experimental design with a pretest-posttest control group design approach. The pretest was conducted in the intervention group and the control group regarding the baby's weight gain before massage. Posttest will be conducted in both groups after the intervention is given. Results: The results of the normality test of the data with the Shapiro-Wilk test in the experimental group from each measurement and the increase showed that they were not normally distributed (p<0.05); while the control group whose data were normally distributed were on the 2nd Week, 3rd Week, and 4th Week measurements, while the others were not normally distributed. For comparison of the baby's weight from each measurement because the treatment group was not normally distributed, the statistical test used was a non-parametric test with the Mann-Whitney test. Conclusions The weight gain of infants aged 3 to 5 months in the intervention group who received massage was greater than in the control group who did not receive massage.